Effect of Integrated Antenatal Care Training on Midwife Service Quality Improvement - Melsa Sagita Imaniar; Hadi Susiarno; Adhi Pribadi; Herry Herman; Dida Akhmad Gurnida; Hadyana Sukandar (Global Medical & Health Communication (GMHC), 2020)
Antenatal care (ANC) is the most effective strategy for preventing complications in pregnancy. However, the current quality of midwife antenatal care services is still considered low. One of the indicators used for assessing midwifery service quality is the technical competency indicator that includes history taking, physical examination, case management and follow up, examination recording, and effective information, communication, and education (IEC). This study aimed to measure the effect on integrated antenatal care training on the quality of midwife services. The design was a pre-test and post-test quasi-experimental study conducted in Manonjaya Public Health Center, Tasikmalaya district, from November to December 2017. Simple random sampling was applied to get 20 respondents for each intervention and control groups. The bivariate analyses used in this study were the paired t test and the Mann-Whitney test. Results showed an overall increase in service quality scores in the intervention and control groups by 5.5% and 0.86%, respectively, with a significant difference in the increase between the two groups (p<0.05). Therefore, there is a significant increase in the quality of midwife after implementing the integrated ANC module and training to midwives. PENGARUH PELATIHAN ANTENATAL CARE TERPADU TERHADAP PENINGKATAN KUALITAS PELAYANAN BIDANAntenatal care (ANC) merupakan strategi pencegahan komplikasi dalam kehamilan paling efektif. Namun, kualitas pelayanan antenatal care bidan saat ini dinilai masih rendah. Salah satu indikator yang digunakan untuk menilai kualitas pelayanan kebidanan adalah indikator kompetensi teknis yang meliputi anamnesis, pemeriksaan fisik, penatalaksanaan dan tindak lanjut kasus, pencatatan pemeriksaan, serta komunikasi, informasi, dan edukasi (KIE) yang efektif. Penelitian ini bertujuan mengukur pengaruh pelatihan antenatal care terpadu terhadap kualitas pelayanan bidan. Desain penelitian ini menggunakan pre-test and post-test quasi-experimental yang dilaksanakan di Puskesmas Manonjaya Kabupaten Tasikmalaya dari November hingga Desember 2017. Pengambilan sampel dilakukan secara simple random sampling untuk mendapatkan 20 responden untuk tiap-tiap kelompok intervensi dan kontrol. Analisis bivariat yang digunakan dalam penelitian ini adalah uji t berpasangan dan Uji Mann-Whitney. Hasil penelitian menunjukkan peningkatan skor kualitas pelayanan secara keseluruhan pada kelompok intervensi dan kontrol sebesar 5,5% dan 0,86% masing-masing dengan perbedaan peningkatan yang signifikan antara kedua kelompok (p<0,05). Simpulan, terdapat peningkatan kualitas bidan yang signifikan setelah penerapan modul ANC terintegrasi dan pelatihan kepada bidan.